One step forward, two backwards. The global development agenda, second half of 2017 - Prado Lallande, Juan Pablo (Revista Española de Desarrollo y Cooperación, 2023)
From April to October 2017, the global development agenda consisted on a dynamic range of events that, although it registered propositive actions, was also characterized by strong clashes, especially comming from the United States, under the presidency of Donald Trump.The evolution of events during this period is the aim of this article, which can be summarized in that nevertheless the global development agenda took a step forward, it took steps back as well, affecting the path to a more sustainable world.